2021
DOI: 10.1038/s41598-021-81574-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium oocysts respond with dormancy to crowding and nutritional stress

Abstract: Malaria parasites develop as oocysts in the mosquito for several days before they are able to infect a human host. During this time, mosquitoes take bloodmeals to replenish their nutrient and energy reserves needed for flight and reproduction. We hypothesized that these bloodmeals are critical for oocyst growth and that experimental infection protocols, typically involving a single bloodmeal at the time of infection, cause nutritional stress to the developing oocysts. Therefore, enumerating oocysts disregardin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 50 publications
3
39
0
Order By: Relevance
“…In addition to the impacts on immune recognition of Plasmodium oocysts associated with an additional blood meal, several recent studies have demonstrated that an additional feeding can also influence parasite growth [ 26 , 32 , 33 ]. In mosquitoes receiving an additional blood meal, P .…”
Section: Malariamentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the impacts on immune recognition of Plasmodium oocysts associated with an additional blood meal, several recent studies have demonstrated that an additional feeding can also influence parasite growth [ 26 , 32 , 33 ]. In mosquitoes receiving an additional blood meal, P .…”
Section: Malariamentioning
confidence: 99%
“…In mosquitoes receiving an additional blood meal, P . falciparum oocysts display increased size [ 26 , 32 , 33 ] as a result of the added nutrient resources provided with feeding, which overcome nutritional dormancy to promote parasite growth [ 33 ]. The resulting increased growth translates into an accelerated sporozoite invasion of the mosquito salivary glands, reducing the EIP and increasing the likelihood of malaria transmission [ 32 ] ( Fig 2 ).…”
Section: Malariamentioning
confidence: 99%
See 2 more Smart Citations
“…For example, insecticide resistance is expected to reduce insecticide-induced mosquito mortality and thus increase the transmission potential of diseases. However, delayed mortality due to insecticide exposure has frequently been observed across different mosquito species (see for instance, Agnew et al, 2004 ; Martins et al, 2012 ) and may result in a reduced disease transmission given malaria parasites’ relatively long incubation time within the mosquito host (ranging from 7 days to several weeks, depending on temperature [ Mordecai et al, 2013 ; Paaijmans et al, 2009 ] and frequency of blood-meal intake [ Habtewold et al, 2021 ; Shaw et al, 2020 ]). Alarmingly though, recent observations of highly pyrethroid-resistant mosquito populations from Burkina Faso show a lack of such delayed mortality in some populations ( Hughes et al, 2020 ).…”
Section: From Controlled Bioassays To Field Reality: Spatio-temporal Variation In Resistancementioning
confidence: 99%